Space, Narrative, and Historical Imagination in Livy's Ab Urbe Condita - Fabrizi, Virginia, (Classical Studies E-Books Online, Collection 2025, 2025)
The surviving books of Livy's Ab Urbe Condita (written ca. 30 - 15 BCE), narrate the origins of Rome, the gradual growth of the city, and its rise to Mediterranean hegemony. This monograph reads Livy's work as, among other things, a narrative about space - the space of the city and the space of the world which Rome strives to conquer and control. Using a narratological approach, it analyses how the text constructs the settings of historical events through an interplay of historical information, literary or conventional elements, and spatial semantics. In this way, it sheds light on Livy's interpretation of politics, empire, conquest, and Roman identity.